12-month prevalence of nicotine dependence and withdrawal among female university students living in dormitory - Kaya, Nazmiye; Çilli, Ali Savaş (Journal of Dependence, 2004)
Objective: In this study, 12-month prevalence rates of nicotine dependence and withdrawal according to DSM-IV criteria has been investigated among female university students living in a dormitory.Method: 299 female students who were selected randomly from a university dormitory have been interviewed using 12-month version of CIDI (Composite International Diagnostic Interview) 2.1.Results: 28.4 % of the students have reported daily use of cigarette for a period of at least four weeks during the last year (regular users). The 21.1 % of students had nicotine dependence and 5.7 % had nicotine withdrawal. The proportions of nicotine dependence and nicotine withdrawal among those who use cigarette regularly were %74.1 and %20 respectively. The mean age for nicotine dependence and nicotine withdrawal was 18±2.3 and 18±2.5 years. Nicotine dependence was found to be increasing significantly with age. 69.4% of the regular smokers had attempted to quit smoking. Of these, 91.5% reported at least one withdrawal symptom. The most common nicotine withdrawal symptoms were craving for tobacco, restlessness and anxiety.Conclusion: Our study indicates that the prevalence of cigarette smoking, nicotine dependence and withdrawal are higher among female university students living in dormitory than the previously reported rates of the same among general university student population. Our study indicates that dormitory life is a risk factor for nicotine dependence and it should be taken into account in prevention of this disorder.
Keywords: Nicotine dependence; nicotine withdrawal; tobacco use; female students; prevalence; dormitory